INFLUENCE OF TELEVISION ADVERTISING ON CONSUMER BUYING BEHAVIOUR OF DANO MILK IN ENUGU EAST LOCAL GOVERNMENT AREA OF ENUGU STATE - Isiani, Grace Amarachi; Asogwa, Joel; Uchendu, Chinelo Ebele (EBSU Journal of Social Sciences and Humanities, 2025)
This study examined the influence of television advertising on consumer buying behaviour of Dano milk in Enugu East Local Government Area of Enugu State. The study was anchored on research. Both qualitative and quantitative research designs were as well employed. Taro Yamani formula of sample size determination was used to calculate the sample size of 390 for the study of which 388 copies of the questionnaire were considered valid and was used for the analysis. The data obtained were analyzed using tables and simple percentage. The researcher found out that majority of Enugu East LGA residents were highly exposed to television advertisements on DSTV channel 154 Africa Magic Family. The researcher also discovered that high price of Dano milk and lack of access to the advertisement since it was on DSTV channel, environment among others are the major inhibitors that affects consumer buying behaviour of the product. The researcher therefore recommended that advertisement of this nature should be done on local television channels so as to enhance large viewership since DSTV subscription is high and not everyone can afford it. Secondly, that Arla Nigeria Plc should be considerate in placement of prices on their product so as to increase high purchasing habit.